Carbon nanomaterials incorporated specialty optical fibers for environmental sensing applications - Tan, Yung Chuen (2017)
The role of optical fibers as a medium for information transfer has found many applications in the world today. One of these applications is in environmental sensing, where slight perturbations in the ambient environment can be remotely detected through modulation of light at selected points along the optical fiber cable. These perturbations exist in the form of variations in refractive index (RI), temperature or strain. This thesis presents several optical fiber-based RI sensors, consisting of long period fiber gratings (LPFGs), Mach-Zehnder Interferometers (MZIs) and multimode interferometers (MMIs), which are individually fabricated from photonic crystal fibers (PCFs) or multimode fibers (MMFs), integrated with carbon nanomaterials. The integration process involved the deposition of a carbon nanotube (CNT) overlay on LPFGs, PCF-MZIs and MMF-MMIs, and multilayer graphene (MG) overlay on PCF-MZIs. These carbon nanomaterials with their unique properties modified the sensing scheme of the conventional sensors, allowing them to gain immunity from certain free spectral range limitations, extend their operation range and also present the potential for dual parameter sensing. For the CNT-deposited LPFGs and PCF-MZIs, the maximum achievable sensitivity within the RI range of 1.33 to 1.42 was approximately 47 dB/RIU and 24.2 dB/RIU, respectively. The maximum achievable sensitivity for the MG-deposited PCF-MZIs was approximately 17.5 dB/RIU within the RI range of 1.33-1.43. For the MMF-MMIs, the maximum achievable sensitivity was approximately 98.8 dB/RIU within the RI range of 1.33 to 1.46. These modified sensors were not only able to continuously measure variations in RI of their ambient environment while only acquiring errors mainly from source power fluctuations, but also exhibited comparable performances in terms of their stability, repeatability and reproducibility.